Investigation of structural and optical properties of boron-doped ZnO nanomaterials synthesized by hydrothermal method - Kati, Nida; Ayten, Busra (Elsevier, 2025)
This study investigates the structural and optical properties of undoped and boron-doped ZnO nanopowders synthesized by hydrothermal methods. ZnO nanopowders in undoped form and with boron doping 1%, 2% and 5% are produced and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and ultraviolet-visible (UV-Vis) spectroscopy. XRD analysis reveals that all samples exhibit a hexagonal wurtzite structure, whereas boron doping causes a reduction in crystal quality and size. SEM imaging shows the formation of hexagonal rod-like structures, with an increase in boron concentration leading to more homogeneous and orderly particles. The EDS results confirm the successful incorporation of boron into the ZnO lattice. UV-Vis spectroscopy demonstrates that boron doping increases absorption and reflection while decreasing the band gap energy from 3.24 eV (undoped) to 3.21 eV (5% doped). The study reveals an inverse relationship between crystal size and both dislocation density and micro-strain with increasing boron doping concentration. These findings contribute to the understanding of how boron doping affects the structural and optical properties of ZnO nanomaterials, with potential implications for their use in various nanotechnology applications such as photocatalysis, piezoelectric devices, and optoelectronics.
Keywords: ZnO; Boron; Hydrothermal method